Unwanted: epistemic erasure of black radical possibility in criminology - Williams, Jason M. (Abolish criminology, 2022)
This chapter unpacks the importance of critically assessing epistemology in criminology. I utilize some examples from my journey in criminology to critique mainstream epistemic frameworks in the discipline. I argue for a future of Black radical epistemologies while also foregrounding the importance of the self and marginalized histories and traditions.